2019
DOI: 10.1186/s13148-019-0772-4
|View full text |Cite
|
Sign up to set email alerts
|

Machine-learned analysis of global and glial/opioid intersection–related DNA methylation in patients with persistent pain after breast cancer surgery

Abstract: BackgroundGlial cells in the central nervous system play a key role in neuroinflammation and subsequent central sensitization to pain. They are therefore involved in the development of persistent pain. One of the main sites of interaction of the immune system with persistent pain has been identified as neuro-immune crosstalk at the glial-opioid interface. The present study examined a potential association between the DNA methylation of two key players of glial/opioid intersection and persistent postoperative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 73 publications
0
11
2
1
Order By: Relevance
“…While variations in gene expression of COMT have been associated with persistent pain following cardiac [24] and breast cancer surgery [25,26], this association was not identified in the present study. Neither pain nor persistent opioid use was associated with COMT or OPRM1 genotypes.…”
Section: Resultscontrasting
confidence: 75%
“…While variations in gene expression of COMT have been associated with persistent pain following cardiac [24] and breast cancer surgery [25,26], this association was not identified in the present study. Neither pain nor persistent opioid use was associated with COMT or OPRM1 genotypes.…”
Section: Resultscontrasting
confidence: 75%
“…Even if related to cancer pain, the experiment of Kringel and coworkers (2019) should also be considered because of the prospective design, which may provide more definitive answers to questions of causality. The study confirmed the predictive utility of epigenetic testing in a sample of 140 women who had undergone breast cancer surgery [35]. DNA methylation quantification was performed in the retrotransposon LINE1, a retrotransposon used as a marker of global DNA methylation being in approximately half a million copies across the human genome [66].…”
Section: Human Studiesmentioning
confidence: 55%
“…Analyzing the identified papers, three main categories were evidenced and grouped in Tables 1-3, respectively: (i) studies investigating epigenetic changes in animal models ( 16), (ii) studies involving human subjects (3), and (iii) studies related to intergenerational or transgenerational prescribed opioid effects (5). Among the three studies on human subjects, one was related to cancer pain patients [35]. Nevertheless, it was included because considered relevant.…”
Section: Gene Expression Female Adolescent Sprague Dawley Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies have successfully used ML strategies to predict chronic pain symptoms and development (e.g., post-surgical and rheumatoid arthritis) [27][28][29][30][31][32]. Lötsch and colleagues [27] used a ML approach to successfully categorize patients into persistent pain versus non-persistent pain groups after breast cancer surgery; the most relevant predictors included age, body mass index, depression, and anxiety.…”
Section: Introductionmentioning
confidence: 99%